2010
DOI: 10.4322/actalb.02201011
|View full text |Cite
|
Sign up to set email alerts
|

Benthic diatom community structure and habitat preferences along an urban pollution gradient in the Monjolinho River, São Carlos, SP, Brazil

Abstract: Aims: The objective of this study was to assess the effects of substrate selection on benthic diatom community structure along an urban pollution gradient. Methods: Substrate assessment, diatom and water sampling was done four times, two times in September and October/08 and two times in May and June/09. Species substrate preference was determined using the Indval method. Benthic diatom community structure (species richness, diversity and equitability) in relation to pollution levels was also evaluated. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
2
4
0
2
Order By: Relevance
“…A espécie tem sido amplamente reportada no Brasil, nas regiões Nordeste, Sudeste e Sul , tanto no plâncton quanto no perifíton de rios e represas (Landucci & Ludwig 2005). Para o Estado de São Paulo foi reportada em ambientes lóticos e lênticos (Bicudo et al 1993, Bere 2010, Bere & Tundisi 2010. A espécie ocorreu em 100% das amostras (tabela 2), apresentando maiores abundâncias no plâncton no período do inverno.…”
Section: Resultsunclassified
“…A espécie tem sido amplamente reportada no Brasil, nas regiões Nordeste, Sudeste e Sul , tanto no plâncton quanto no perifíton de rios e represas (Landucci & Ludwig 2005). Para o Estado de São Paulo foi reportada em ambientes lóticos e lênticos (Bicudo et al 1993, Bere 2010, Bere & Tundisi 2010. A espécie ocorreu em 100% das amostras (tabela 2), apresentando maiores abundâncias no plâncton no período do inverno.…”
Section: Resultsunclassified
“…N. cryptotenella has solitary life form Lange et al, 2011) and can move quickly to favorable light and nutrient habitat (Johnson et al, 1997). Due to this character, it is often observed in kinetically unstable epipelic substrates as a pioneering colonizer (Hermany et al, 2006;Passy, 2007;Bere, 2010), and was observed to increase at timings of sandy sediment deposition (Brancelj et al, 2000). On the other hand, it is also found from top surfaces of thick algal mat over epiphytic or epilithic substrate (Garrido et al, 2013) probably in favor of higher illumination and nutrient.…”
Section: Suspension Of Littoral Diatom Fossilsmentioning
confidence: 98%
“…The contributions range from rivers (Souza & Senna 2009, Bere 2010, Bere & Tundisi 2010 to reservoirs (Graça et al 2007, Moutinho et al 2007, Fontana & Bicudo 2009, Almeida & Bicudo 2014) and other environments (e.g., Morandi et al 2006, Rocha & Bicudo 2008). In reservoirs, most studies address planktonic or periphytic diatoms and lately have included diatoms from sediments (Fontana & Bicudo 2009, Almeida & Bicudo 2014, Faustino et al 2016.…”
Section: Introductionmentioning
confidence: 99%